Effect of Calcination Temperature on the Adsorption Performance of Tanggamus Natural Zeolite for Ammonium Removal from Shrimp Pond Wastewater - Al Qadri, Latif; Abelta, Gita Aldira; Febrina, Melany; Rajak, Abdul; Maulana, Sena; Asagabaldan, Meezan Ardhanu; Taher, Tarmizi (Science and Technology Indonesia, 2024)
This research explores the potential of locally sourced natural zeolite from the Tanggamus District, Indonesia, for the removal of ammonium from shrimp pond wastewater. The study utilizes a comprehensive approach involving desilication modification, batch adsorption experiments, and field-scale application. The zeolite, predominantly composed of clinoptilolite, undergoes calcination at varying temperatures, with 200°C proving to be optimal for enhancing ammonium adsorption capacity. The study also highlights the efficient use of zeolite at a lower dosage of 5 g/L, yielding high removal efficiency. The real-world effectiveness of this method was confirmed by field experiments, where the application of calcined zeolite resulted in lower ammonium concentrations in shrimp ponds. The results demonstrate that the application method, specifically direct spreading in the ponds, affects adsorption performance. These findings underscore the potential of using Tanggamus Natural Zeolite as a cost-effective and eco-friendly solution for ammonium control in shrimp pond wastewater. This work paves the way for future research focusing on the long-term application effects and zeolite regeneration methods to further improve the economic and environmental efficiency of this approach.